Extracellular matrix as the early structural marker for Centella asiatica embryogenic tissues - Lai, Kok Song; Yusoff, Khatijah; Mahmood, Maziah (Springer Netherlands, 2011)
Embryogenic and non-embryogenic calli were induced from the Centella asiatica leaf explants on Murashige and Skoog medium supplemented with kinetin and 2,4-dichlorophenophenoxyacetic acid. The extracellular matrix (ECM) layer was seen on the surface of embryogenic cells but not on the non-embryogenic cells. The ECM formed bridges with net-like material between the embryogenic cells. This network like structure was believed to play an important role in plant morphogenesis and can serve as an early structural marker of embryogenic competence in Centella asiatica calli culture.